Comprehensive Analysis of Survival-Related lncRNAs, miRNAs, and mRNAs Forming a Competing Endogenous RNA Network in Gastric Cancer - Zhao, Yanjie; Zhang, Heng; Ju, Qiang; Li, Xinmei; Zheng, Yuxin (Frontiers in Genetics, 2021)
To analyze and construct a survival-related competing endogenous RNA (ceRNA) networks in gastric cancer (GC) with lymph node metastasis, we obtained expression profiles of Long non-coding RNAs (lncRNAs), mRNAs, microRNAs (miRNAs) in GC from The Cancer Genome Atlas (TCGA) database. The edgeR package was used to screen differentially expressed lncRNAs (DE-lncRNAs), mRNAs (DE-mRNAs) and miRNAs (DE-miRNAs) between GC patients with lymphatic metastasis and patients without lymphatic metastasis. Then we utilized univariate cox regression analysis to find the survival-related differentially expressed RNAs (DE-RNAs). In addition, we used multivariate cox regression analysis to screen 3 lncRNAs, 2 miRNAs and 3 mRNAs to construct prognostic prediction models. Results showed that 2247 lncRNAs ,155 miRNAs and 1253 mRNAs were differentially expressed. Using univariate cox regression analysis, we found 395 lncRNAs, 8 miRNAs and 180 mRNAs were significantly related to survival time of GC patients. We next created a survival-related network consisting of 59 lncRNAs, 7 miRNAs and 36 mRNAs. In addition, we identified 8 RNAs associated with prognosis by multivariate cox regression analysis, including 3 lncRNAs (AC094104.2, AC010457.1, AC091832.1), 2 miRNAs (miR-653-5p, miR-3923) and 3 mRNAs (C5orf46, EPHA8, HPR), to construct prognostic prediction model respectively. The risk scores could be used to assess the GC patient's prognosis. In conclusion, this study provides new insights for the research of ceRNA network in GC and novel clues for the screening of prognostic biomarkers for GC.